Polygonumins A, a newly isolated compound from the stem of Polygonum minus Huds with potential medicinal activities - Ahmad, Rafidah; Sahidin, I.; Bakhtiar, M. Taher; Low, Chen Fei; Mohd Noor, Normah; Sillapachaiyaporn, Chanin; Chuchawankul, Siriporn; Sarachana, Tewarit; Tencomnao, Tewin; Iskandar, Faizah; Rajab, Nor Fadilah; Baharum, Syarul Nataqain (Nature Publishing Group, 2018)
Polygonumins A, a new compound, was isolated from the stem of Polygonum minus. Based on NMR results, the compound’s structure is identical to that of vanicoside A, comprising four phenylpropanoid ester units and a sucrose unit. The structure diferences were located at C-3″″′. The cytotoxic activity of polygonumins A was evaluated on several cancer cell lines by a cell viability assay using tetrazolium dye 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT). The compound showed the highest antiproliferative (p<0.05) activities against K562 (Human Leukaemia Cell Line), MCF7 (Human breast adenocarcinoma cell line), and HCT116 (Colorectal cancer cells) cells. Cytotoxic studies against V79–4 cells were carried out and showed that polygonumins A was toxic at 50µg/ml, suggesting that this compound may be used as an anticancer drug without afecting normal cells. Polygonumins A also showed promising activity as an HIV-1 protease inhibitor with 56% relative inhibition. Molecular docking results indicated that the compound possesses high binding afnity towards the HIV protease over the low binding free energy range of -10.5 to -11.3kcal/mol. P. minus is used in Malaysian traditional medicine for the treatment of tumour cells. This is the frst report on the use of P. minus as an HIV-1 protease inhibitor.